1990
DOI: 10.1177/014107689008300308
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Cancer after Pelvic Irradiation

Abstract: During a 6 month period in 1988 five women were treated at Colchester General Hospital for carcinoma of the rectum, each more than 10 years after undergoing pelvic irradiation. Although irradiation has not been proven to induce human colorectal cancer, considerable circumstantial and experimental evidence supports this belief. Features suggestive of radiation-induced colorectal cancer are the presence of radiation-damaged bowel adjacent to the carcinoma and a mucus-secreting ('colloid') histological pattern. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In the present case, the two flat sigmoid tumors had a diffusely infiltrating appearance, without a well-defined tumor margin. Levitt et al (7) found synchronous multiple rectal cancers within the radiation fields in 2 of 5 patients with rectal cancer following pelvic irradiation, and hypothesized that radiation exerted a ‘field effect’ for carcinogenesis on the rectal mucosa. In the present case, the two flat tumors and 6 flat polyps were all observed in the resected specimens and, thus, the radiation field effect may be involved in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, the two flat sigmoid tumors had a diffusely infiltrating appearance, without a well-defined tumor margin. Levitt et al (7) found synchronous multiple rectal cancers within the radiation fields in 2 of 5 patients with rectal cancer following pelvic irradiation, and hypothesized that radiation exerted a ‘field effect’ for carcinogenesis on the rectal mucosa. In the present case, the two flat tumors and 6 flat polyps were all observed in the resected specimens and, thus, the radiation field effect may be involved in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact incidence of this complication and the mechanisms of tumorigenesis have not been fully elucidated, a close association between radiation and the development of colorectal cancer (CRC) has been demonstrated (6,7). Post-irradiation cancer is currently termed radiation-associated cancer, as other predisposing factors, such as lymphedema, adjuvant chemotherapy and genetic abnormalities may be involved (8).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the spectrum of genetic aberrations between animal models and humans may indicate species differences. Levitt et al 3 found synchronous multiple rectal cancers within the irradiated fields in two of five patients with rectal cancer after pelvic irradiation, and speculated that radiation had a "field effect" for carcinogenesis in the rectal mucosa. However, in the present study, four tumors that had K-ras or p53 mutation did not show the same genetic change in irradiated normal mucosa adjacent to the carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…LOH was indicated by more than 50% allelic imbalance in the tumor compared to normal tissue. (A) 8 in the hMSH3 gene, (A) 10 and (GT) 3 in the TGF RII gene, and (G) 8 in the BAX gene were examined by polymerase chain reaction single-strand conformation polymorphism (PCR-SSCP) analysis. 4,14,15 The hMSH3 gene is one of the mismatch repair genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation